GENDER ASPECTS IN TRANSLATION - Professor Nuri TINAZ; Kenjayeva Adolat Asrorovnsa; Alimova Kamola Tursunovna (Western European Studies, 2024)
The article examines gender features of the translation of texts. Translating a work of fiction is a complex process, and translators often resort to using various types of transformations. So, in some cases, the translation of works makes it possible to determine the gender of the translation, and will reveal the peculiarities of the translation of women and men. Translation of a poem in most cases fluctuates between two extreme principles: a word-forword accurate, but artistically inferior translation and an artistically complete, but far from the original, free translation. These two principles are reflected in two main points of view: the definition of translation from a linguistic and literary perspective.
Keywords: gender aspect; translation; gender issues